Does privatization of public sector banks affect stock prices? An event study approach on the Indian banking sector stocks - Varun Kumar Rai; Dharen Kumar Pandey (Asian Journal of Accounting Research, 2021)
With a sample of 22 banks, this study examines the significance of the news contents about the privatization of two public sector banks in India. New information does impact the stock markets. This study provides evidence on how the privatization of public sector banks impacted the returns of the Indian banking sector.This study employs the standard event study methodology with the market model for estimating the normal returns.The statistical results indicate that while the private sector banks experienced positive average abnormal returns on the event day, the cumulative effect of the announcement is negatively significant for both private and public sector banks. The statistical results also provide evidence of information leakage, with significant results before the announcement date. The shorter event windows analysis exhibits significant positive returns in the 5-days [âˆ’2, +2] window for the private sector banks and the entire sample, signifying a positive short-term impact on the private sector banks.The event study literature captures the impacts of many events. However, to the best of our knowledge, the impacts of the privatization of the Indian public sector banks have never been examined using the event study methodology. Hence, this study anticipates being the first-ever study to fill this gap and extend the available literature in finance. In addition, although we provide Indian evidence, future studies may be oriented to capture cross-country impacts.